2016
DOI: 10.1590/1089-6891v17i321194
|View full text |Cite
|
Sign up to set email alerts
|

Conformação Corporal De Equinos De Diferentes Grupos Genéticos

Abstract: Resumo Qualquer atividade equestre exig e equino com aptidão adequada, podendo ser identificada através da conformação corporal (IC), calculada pela combinação de medidas biométricas. Objetivou-se avaliar IC de 86 equinos, pertencentes aos grupos genéticos (GG): Crioulo (CR), Brasileiro de Hipismo (BH), Árabe (ARB), Quarto de Milha (QM), Puro Sangue Inglês (PSI) e mestiços com pequena estatura corporal, rotulado Petiço (PE). Avaliaram-se relação cernelha garupa, peso corporal estimado, torácico, corporal, corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In this study, population of CAM horses, males and non-pregnant females, had BI that classified them as small in stature (BI<85) and matched a conformation closer to traction/load as described by Rezende et al (2016) (Table 1). Considering DTI, animals of both sexes were hypometric, small, and slim (DTI<10.5) as they approached adulthood.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, population of CAM horses, males and non-pregnant females, had BI that classified them as small in stature (BI<85) and matched a conformation closer to traction/load as described by Rezende et al (2016) (Table 1). Considering DTI, animals of both sexes were hypometric, small, and slim (DTI<10.5) as they approached adulthood.…”
Section: Discussionmentioning
confidence: 90%
“…Measurements of WH and BW in the present study were lower than those reported for mules in Cuba (BW: 345 kg) (Ramajo et al, 2000) and Venezuela (WH: 148 cm and BW: 275 kg) (Pineda & Florio-Luis, 2016). These differences can be explained by the effect the parental genetic group (Rezende et al, 2018), which could be reflected on mules body measurements.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing PI, it's noteworthy its behavior as a more independent variable. Other possibilities of multivariate analysis have been reported in horses, in order to evaluate the morphofunctional diversity of animals from different genetic composition, aiming to identify a better biotype for the Pantanal region of Brazil (Rezende et al, 2018).…”
Section: Resultsmentioning
confidence: 99%